Pricing and service effort strategy in a dual-channel supply chain with showrooming effect - Li, Guo; Li, Lin; Sun, Jiasen (Transportation research. Part E, Logistics and transportation review, 2019)
•This study constructs stylized Stackelberg models in a dual-channel supply chain.•Three service effort strategies for the retailer are discussed and compared.•Both the manufacturer and retailer benefit more in the ex-post service effort strategy.•The manufacturer will set a low wholesale price in the ex-post service effort strategy.•The greater the showrooming effect is, the higher profits firms will obtain in the ex-post service effort strategy. This study investigates the influence of the showrooming effect on firms’ pricing and service effort in a dual-channel supply chain. The no-service, ex-ante and ex-post service effort strategies are considered. The equilibrium results show that the showrooming effect enables the firms to benefit the most from the ex-post service efforts. Moreover, the showrooming effect makes the manufacturer set high/low wholesale prices for retailers in the ex-ante/ex-post strategy. This study further extends the three strategies by considering no showrooming effect. Results show that the greater the showrooming effect, the higher profits firms will obtain using the ex-post service effort strategy.